2012
DOI: 10.1183/09031936.00176111
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in primary ciliary dyskinesia

Abstract: Nitric oxide is continually synthesised in the respiratory epithelium and is upregulated in response to infection or inflammation. Primary ciliary dyskinesia (PCD) is characterised by recurrent sinopulmonary infections due to impaired mucociliary clearance. Despite chronic infections, nasal nitric oxide in such patients is markedly reduced and is used as a screening test for this condition. These low levels were first described .15 yrs ago but the underlying mechanisms have yet to be fully elucidated. We revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
105
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 141 publications
0
105
1
7
Order By: Relevance
“…For the confirmed PCD group with defined ultrastructural defects in the ciliary axonemes, the mean nNO level (20.0 nl/ min) is less than 10% of the mean nNO measurement for healthy control subjects (304.6 nl/min) with minimal overlap. Previous reports in smaller subsets show a similar magnitude of difference between PCD and healthy control subjects (7)(8)(9)(10)(11)(12). The cutoff value defined in this study (77 nl/min) is slightly lower than what was identified in our earlier study that examined a smaller patient population (7).…”
Section: Original Researchmentioning
confidence: 59%
See 3 more Smart Citations
“…For the confirmed PCD group with defined ultrastructural defects in the ciliary axonemes, the mean nNO level (20.0 nl/ min) is less than 10% of the mean nNO measurement for healthy control subjects (304.6 nl/min) with minimal overlap. Previous reports in smaller subsets show a similar magnitude of difference between PCD and healthy control subjects (7)(8)(9)(10)(11)(12). The cutoff value defined in this study (77 nl/min) is slightly lower than what was identified in our earlier study that examined a smaller patient population (7).…”
Section: Original Researchmentioning
confidence: 59%
“…The nNO values in some of the patients with CF, however, did overlap with PCD values, which has been described in other studies (7)(8)(9)11). Therefore, CF must be excluded by a quantitative pilocarpine iontophoresis sweat test or CFTR genotype testing in all individuals with nNO measurements below the cutoff values.…”
Section: Original Researchmentioning
confidence: 82%
See 2 more Smart Citations
“…Whilst the reason for reduced nNO remains elusive [27], measurement became widely established as a screening test [11,17,19,[28][29][30][31]. A recent meta-A c c e p t e d M a n u s c r i p t analysis of 11 studies comparing nNO during a velum closure breath hold reported a mean nNO output of 19 nl/min (SD 18.6) in PCD (n=478) and 265 nl/min (SD 118.9) in healthy controls (n=338) [32].…”
Section: Page 5 Of 36mentioning
confidence: 99%